Reducing Global Warming Potential through Sustainable Intensification of Basmati Rice-Wheat Systems in India - Sapkota, Tek Bahadur; Shankar, Vivek; Rai, Munmun; Jat, Mangi Lal; Stirling, Clare M.; Singh, Love Kumar; Jat, Hanuman Sahay; Grewal, Mohinder S. (MDPI, 2017)
This study examines the effects of tillage, residue management and cropping system intensification through the inclusion of green gram on the performance of the rice-wheat (RW) system in NW India. We hypothesized that zero tillage (ZT) with residue retention provides a means of sustainably intensifying the RW system through lower production costs and higher economic profitability, whilst at the same time minimizing soil and environmental trade-offs. To test this hypothesis, we evaluated six combinations of tillage, residue management and green gram integration in RW rotation in northwest Indo-Gangetic Plains (IGP) of India. Treatments included in the study were: rice and wheat under conventional tillage (CT) with and without green gram (CTR-CTW, CTR-CTW+GG), both crops under zero-tillage (ZT) with and without green gram (ZTR-ZTW-R, ZTR-ZTW-R+GG) and both crops under ZT plus residues with and without green gram (ZTR-ZTW+R, ZTR-ZTW+R+GG). Based on two consecutive years of data, the net return from the RW system was significantly higher in the ZT than CT systems. Methane emissions were only observed under flooded conditions in CT rice plots; otherwise, emissions were negligible in all other treatment combinations. N2O emissions were dictated by N fertilizer application with no other treatment effects. Overall, ZT with residue retention resulted in the lowest global warming potential (GWP) ranging from −3301 to −823 kg CO2-eq ha−1 year−1 compared to 4113 to 7917 kg CO2-eq ha−1 year−1 in other treatments. Operational inputs (tillage, planting, and irrigation) and soil C sequestration had significant effects on total GWP. The water footprint of RW production system was about 29% less in CA-based system compared to CT-based systems. Our study concludes that ZTR-ZTW+R and ZTR-ZTW+R+GG in RW systems of northwestern IGP have the potential to be agronomically productive, economically viable with benefits also for the environment in terms of soil health and GHG emissions.